Students' Exploratory Analysis Study of Internet Skills - Loliyana, Loliyana; Sukamto, Ismu (Universitas Negeri Malang, 2020)
The purpose of this study was to describe the internet skills of students. The method used was a survey with an exploratory research design. The research sample consisted of 166 students. The research instrument was adapted (Van Deursen et al., 2016) which is composed of 5 indicators, namely: (1) operational internal skills; (2) formal internet skills; (3) informational internet skills; (4) communicational internet skills; and (5) content creation internet skills. The results showed that students had good internet skills, including operational, formal, communicational, and informational skills. Nevertheless, it was necessary to develop creative skills so that students are more productive in creating or developing content in a digital environment. In addition, there was a positive relationship between operational and communicational skills and con-tent creation skills. Thus, it can be concluded that overall, students have good basic internet skills. However, further research is needed to find out how these variables affect other variables.